2016
DOI: 10.1302/0301-620x.98b3.35818
|View full text |Cite
|
Sign up to set email alerts
|

Improving the care of patients with severe open fractures of the tibia

Abstract: This study demonstrates that a systemised trauma network combined with evidence based practice can lead to improvements in patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 18 publications
7
37
1
Order By: Relevance
“…These findings provide the clinician with a greater evidential basis for advising and counselling patients as to their likely outcomes with each of the two alternative treatment strategies. 39 …”
Section: Discussionmentioning
confidence: 99%
“…These findings provide the clinician with a greater evidential basis for advising and counselling patients as to their likely outcomes with each of the two alternative treatment strategies. 39 …”
Section: Discussionmentioning
confidence: 99%
“…First, there is no universal definition of a high-energy trauma. The difference between high- and low-energy trauma was based on literature and at the discretion of the investigators [ 10 , 18 ]. Some of the patient charts lacked a detailed description of the mechanism of injury, which impeded the estimation of the energetic force.…”
Section: Discussionmentioning
confidence: 99%
“…High-energy fractures were defined conform the ATLS ® guidelines and caused by; a motor vehicle-related traffic injury, firearm incident, fall from height >2 m, fall at high speed (e.g., fall with bicycle), aircraft accident, a crash with an object at high speed or a crash with a heavy object [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported successful results of major trauma centres (MTC) in the United Kingdom following these standards. A decrease in treatment time, fewer required surgeries per patient, and a higher successful limb reconstruction rate have led to a decrease in deep infection rate [911].…”
Section: Introductionmentioning
confidence: 99%